The anti-fibrotic role of mast cells in the liver is mediated by HLA-G and interaction with hepatic stellate cells. (May 2019) - Amiot, Laurence; Vu, Nicolas; Drenou, Bernard; Scrofani, Maurice; Chalin, Arnaud; Devisme, Christelle; Samson, Michel
Abstract: Background & aims: We have reported a significant association between HLA-G expression or the number of hepatic mast cells and liver fibrosis. Here, we investigated the role of HLA-G and mast cells in liver fibrosis, focusing, in particular, on interactions between human mast and stellate cells. Methods: Human mast cells (HMC cell line, CD34-derived mast cells, or tissue-derived mast cells) were co-cultured with purified human hepatic stellate cells (HSCs), and collagen I production by HSCs was evaluated. Mast cells and HSCs were characterized by immunocytochemistry. Various conditions were tested: different times in direct or indirect contact, presence or absence of cytokines, addition or not of HLA-G, and presence or absence of specific protease inhibitors. Results: The reciprocal interaction between HSCs and mast cells led to the attraction of mast cells to HSCs in vivo and in vitro, and to a significant decrease in collagen production, at all times of co-culture, following the direct or indirect contact of mast cells with HSCs alone or in the presence of TGF-β, IFN-α or IL-10. We identified the diffusible factors involved in collagen I degradation as mast cell proteases. Moreover, HLA-G expression increased during the co-culture of HSCs and mast cells, with HLA-G acting on both mast cells and HSCs, to enhance collagen I degradation. Conclusions: Mast cells play a beneficial, anti-fibrotic role in liver fibrosis, via the HLA-G-mediated decrease of collagen I. These findings are consistent with high levels of cross-communication between mast cells and hepatic stellate cells and the role of HLA-G.